(untitled) (Bangladesh Journal of Child Health, 2019)
Background: Childhood obesity is becoming an epidemic globally as well as in Bangladesh. Although several risk factors are identified for overweight or obesity, limited studies have been done in our country. The objective of this study was to identify the risk factors of overweight and obesity in children and adolescents in Bangladesh. Methodology: It was a cross sectional study done in children, aged 5 to 16 years, attending the Paediatric Endocrine Clinic and Paediatric Outpatient Department, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka over a period of 18 months. Overweight and obese children as well as normal weight children were selected after considering inclusion and exclusion criteria. They were classified as case (overweight/obese) and control (normal weight) according to the Center‘s’ for Disease Control and Prevention age and sex specific growth chart. Among a total of 150 children 100 were cases and 50 were controls. Results: Majority of children in both the groups were male. Among cases 77% were obese and 23% were overweight. Analyzing the risk factors, it was found that first issue had 2.66 times, watching TV >3 hr had 4.47 times, breast feeding <6 month had 4.16 times, daily more caloric intake (approx.) had 17.36 times and maternal BMI >24.9 had 2.70 times increased risk to develop obesity. Conclusion: The first issue, excess television watching, lack of exclusive breast feeding, excess calorie intake and having overweight/obese mother had higher risk to develop overweight or obesity in children and adolescents. Bangladesh J Child Health 2019; VOL 43 (1) :9-14